Upaya Meningkatkan Kompetensi Guru melalui Supervisi Akademik Teknik Individual Kunjungan Kelas di MIN 1 Gunungkidul Tahun Ajaran 2018/2019 - Mujiyana (Jurnal Pendidikan Madrasah, 2019)
Madrasah action research is one of the efforts of the madrasa / Madrasah head in improving the system and learning tools to achieve optimal learning outcomes by teachers who have high competence. This study aims to determine the implementation and results achieved in academic supervision to improve teacher competency in MIN 1 Gunungkidul. The objects in this study were 12 class teachers and 1 PAI teacher. The methodology used is the academic supervision and approaches implemented in two cycles, with each cycle is carried out in four stages, namely planning, implementation, observation, and reflection. The results of the study showed that there was an increase in teacher competence from the results of academic supervision of 13 teachers who were the object of research experiencing increased ability to plan and implement learning. The following capabilities characterize competency enhancement: 1) making lesson plans that are by the rules of curriculum 013, 2) implementing the learning process by the syllabus and lesson plans, and 3) implementing the assessment by the assessment standards.